The Legitimacy Controversy Surrounding Mass Organizations as Holders of Mining Business Licenses within the Framework of National Mining Law - Clarosa, Vivian; Rasji, Rasji (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
This study analyzes the legitimacy of religious-based organizations (ormas) as holders of mining business permits under Law Number 2 of 2025, the Fourth Amendment to Law Number 4 of 2009 on Mineral and Coal Mining. Using a normative juridical approach, it evaluates the policy’s alignment with the constitutional principles of Article 33 of the 1945 Constitution and the framework of good mining governance. The findings indicate that prioritizing Special Mining Business Permit Areas (WIUPK) for business entities owned by religious organizations is formally recognized but substantively fragile. The policy creates risks of political clientelism, conflicts of interest, and environmental harm due to insufficient technical capacity and weak oversight. Normatively, it does not fulfill the constitutional mandate to promote public welfare but instead opens pathways for abuses of authority and the politicization of religion. Strengthening implementing regulations is essential to ensure transparency, accountability, and environmental sustainability in natural resource management.